Learner autonomy in the Vietnamese EAP context: a literature review / Jasper Roe and Mike Perkins - Jasper, Roe; Mike, Perkins (Faculty of Education, 2020)
This literature review explores the current body of research pertaining to learner autonomy in the Vietnamese English for Academic Purposes (EAP) context, investigating themes and research methodologies, conclusions drawn, limitations and possible avenues for further study and new research directions in the future. We demonstrate that although there are many studies exploring the concept of learner autonomy, the definitions as to how this term is described is not clear throughout the literature, and this is a limitation in the current research field. In addition to this, there is significant evidence suggesting that Vietnamese EAP learners are keen to engage in autonomous learning practices and can demonstrate the self-regulation required to do so, which disagrees with traditional conceptions of Confucian heritage culture learning approaches.